Is the Middle Meningeal Artery the Optimal Path for Dural Arteriovenous Fistula Embolization? - Su, Han; Xu, Kan; Wang, Yiheng; Yu, Jinlu (Frontiers in Neurology, 2021)
Background: Currently, the middle meningeal artery (MMA) is considered the optimal arterial path for the endovascular treatment (EVT) of dural arteriovenous fistulas (DAVFs). However, the details are not understood completely. Materials and methods: In this study, a retrospective study was performed of patients who were admitted to the First Hospital of Jilin University diagnosed with a cranial DAVF with MMA involvement as a feeding artery. Based on the arterial path chosen in the first EVT procedure and the role of the MMA in EVT, EVT was divided into three types (I–III), each of which was further divided into two subclasses (a and b). The embolization degree was analyzed. Result: The 104 included patients ranged in age from 13 to 80 years (mean, 53.6 ±11.8 years). Among them, there were 48 cases of hemorrhage (46.2%, 48/104). Complete embolization was achieved in the first procedure in 64.4% of cases, and success was eventually achieved by EVT (the first attempt or a subsequent attempt) in 74.1% of cases. EVT caused complications in 6.7% of cases. A modified Rankin scale score of 0 or 1 was achieved in 78.8% of patients. On statistical analysis, types Ia and IIb EVT had the lowest complete embolization rates, but no difference was shown between types Ia and IIb EVT. Types IIa and III EVT had the highest complete embolization rates. Most cases had a good prognosis. Conclusion: The findings shed light on the features of different EVT classes defined by the first EVT procedure and by the role of the MMA. The delivery of treatment via slim and tortuous MMA branches increased the failure rate of EVT. A thick, straight MMA branch is the optimal path for treatment.